PENGGUNAAN MEDIA GAMBAR DALAM PEMBELAJARAN IPAS UNTUK MENUMBUHKAN PEMAHAMAN TENTANG PENTINGNYA MENGUTAMAKAN KEBUTUHAN PRIMER PADA SISWA KELAS IV SD NEGERI 15 TAMPE - Aigrescia Madeanne Trinawa; Margaretha Lidya Sumarni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the use of picture media in integrated science and social studies learning to foster students’ understanding of the importance of prioritizing primary needs among fourth-grade students at SD Negeri 15 Tampe. This study employed a descriptive qualitative approach involving the principal, the fourth-grade teacher, and fourth-grade students as research subjects. Data were collected through observation, interviews, and documentation. The findings revealed that the use of picture media helped students understand the concept of primary needs, such as food, clothing, and shelter, in a more concrete way. The use of picture media also increased students’ interest and enthusiasm during the learning process. Most students were able to distinguish between primary and secondary needs and began to understand the importance of prioritizing basic needs in daily life. However, some students still experienced difficulties understanding the material when the pictures were not accompanied by explanations or written text. Therefore, the use of picture media in integrated science and social studies learning can improve students’ understanding of primary needs.